2023
DOI: 10.7150/ijbs.79461
|View full text |Cite
|
Sign up to set email alerts
|

Brain-derived extracellular vesicles promote bone-fat imbalance in Alzheimer's disease

Abstract: Inadequate osteogenesis and excessive adipogenesis of bone marrow mesenchymal stem cells (BMSCs) are key factors in the pathogenesis of osteoporosis. Patients with Alzheimer's disease (AD) have a higher incidence of osteoporosis than healthy adults, but the underlying mechanism is not clear. Here, we show that brain-derived extracellular vesicles (EVs) from adult AD or wild-type mice can cross the blood-brain barrier to reach the distal bone tissue, while only AD brain-derived EVs (AD-B-EVs) significantly prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 58 publications
1
9
0
Order By: Relevance
“…Particularly, due to the protection of EVs, they are not only stable in the extracellular environment, such as blood(Chen et al, 2008), but also free to pass through the blood-brain barrier, indicating that miRNAs may work as the linkers between brain and bone. Consistently, a previous study reported that miR-483-5p, stored in brain-derived EVs, could promote bone-fat imbalance in Alzheimer’s disease(Liu et al, 2023). Take the consideration that several endogenic miRNAs in the brain(Olejniczak et al, 2018) and blood(Makrygianni & Chrousos, 2023) were reported to change their expression levels after chronic psychological stress, it’s deducible that psychological stress may interfere the bone metabolism through brain-derived miRNAs.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Particularly, due to the protection of EVs, they are not only stable in the extracellular environment, such as blood(Chen et al, 2008), but also free to pass through the blood-brain barrier, indicating that miRNAs may work as the linkers between brain and bone. Consistently, a previous study reported that miR-483-5p, stored in brain-derived EVs, could promote bone-fat imbalance in Alzheimer’s disease(Liu et al, 2023). Take the consideration that several endogenic miRNAs in the brain(Olejniczak et al, 2018) and blood(Makrygianni & Chrousos, 2023) were reported to change their expression levels after chronic psychological stress, it’s deducible that psychological stress may interfere the bone metabolism through brain-derived miRNAs.…”
Section: Introductionsupporting
confidence: 84%
“…miR-328a-3p and miR-150-5p enriched in EVs from hippocampus after traumatic brain injury accelerate bone healing(Xia et al, 2021). miR-384-5p in brain-derived EVs induces a bone-fat imbalance and bone loss in Alzheimer’s disease (Liu et al, 2023). Psychological stress, one of the most common type of neuropsychiatric disorders, is well established as a promoter of osteoporosis, so could miRNAs act as messengers between it and bone homeostasis?…”
Section: Discussionmentioning
confidence: 99%
“…Insufficient osteogenesis and excessive adipogenesis of bone marrow mesenchymal stem cells (BMSCs) are considered to be key factors in the pathogenesis of OP. 137 Studies have found that activation and blocking of the Notch1 signaling pathway can affect the differentiation of BMSCs. 138 HCG18 has been found to inhibit the differentiation of BMSCs by targeting the miR-30a-5p/NOTCH1 axis.…”
Section: Bone-related Diseasesmentioning
confidence: 99%
“…HCG18, as a ceRNA, can promote the progression of OP. Insufficient osteogenesis and excessive adipogenesis of bone marrow mesenchymal stem cells (BMSCs) are considered to be key factors in the pathogenesis of OP 137 . Studies have found that activation and blocking of the Notch1 signaling pathway can affect the differentiation of BMSCs 138 .…”
Section: Hcg18 In Human Diseasementioning
confidence: 99%
“…These vesicles, encompassing both exosomes (30-100 nm) derived from endosomal compartments and the more heterogeneous ectosomes (50-1000 nm), encapsulate a microcosm of the cellular interior, carrying nucleic acids, proteins, lipids, and metabolites across biological frontiers [8][9][10]. Their repertoire extends beyond mere waste disposal to orchestrating physiological and pathological processes, facilitated by their capacity to breach the blood-brain barrier (BBB) and to mediate crosstalk between the CNS and peripheral tissues [7,8,[11][12][13].…”
Section: Introductionmentioning
confidence: 99%